2013
DOI: 10.1039/c3cc43133a
|View full text |Cite
|
Sign up to set email alerts
|

The decisive role of ligand metathesis in Au/Pd bimetallic catalysis

Abstract: AuClL(1)/PdCl2L(2)2 cocatalyzed coupling of Ar(1)X and Ar(2)SnBu3 is feasible for bulky Ar(1), provided that at least one ligand on Pd is not strongly coordinating. This can be achieved in situ by Au/Pd ligand exchange if L(1) is weakly coordinating. When the exchange is slow, independent preparation of appropriate catalysts is recommended.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(35 citation statements)
references
References 22 publications
0
35
0
Order By: Relevance
“…could not be improved by adjusting electrophile and co-catalyst concentration (see the Supplementary Information, Section 13, for details). This might be because the presence of achiral bis-phosphine Pd species causes an achiral Cu–B(pin) complex to be generated by ligand exchange 18 , and the resulting non-enantioselective pathways offset any advantage that might result from a change in conditions.…”
Section: Resultsmentioning
confidence: 99%
“…could not be improved by adjusting electrophile and co-catalyst concentration (see the Supplementary Information, Section 13, for details). This might be because the presence of achiral bis-phosphine Pd species causes an achiral Cu–B(pin) complex to be generated by ligand exchange 18 , and the resulting non-enantioselective pathways offset any advantage that might result from a change in conditions.…”
Section: Resultsmentioning
confidence: 99%
“…Catalyst 5 is extremely efficient and quite general, as discussed below. It might appear that its composition (two different ligands, one of them AsPh 3 ) corresponds to a highly contaminant and not easily accessible catalyst, but it is very easy to make in two steps from simple precursors, and the isolated cross‐coupling reaction products analyzed by inductively coupled plasma mass spectrometry (ICP‐MS) show that the palladium or arsenic concentrations in the product are <1 μg g −1 (see the Supporting Information for details).…”
Section: Resultsmentioning
confidence: 99%
“…The use of linear gold complexes as "aryl carriers" in this bimetallic catalysis [15] leads to as equential Sn/Au/Pd bulky-aryl doublet ransmetalation,i nw hich eithero ft he two steps is much lessc ongested and has al ower transmetalation barriert han that of direct Sn/Pd transmetalation. [16,17] In this research we found that, for the facilitation of transmetalation to Pd II (Sn/Pdo rA u/Pd), it was important that Pd should contain an ancillary ligand that was easy to displace;a tt he same time, to stabilize the Pd 0 intermediate, good coordinating soft ligands should be availablet oc oordinate to Pd.T his led us to discover the excellent performance of [PdCl 2 (IDM)(AsPh 3 )] (IDM = 1,3-dimethylimidazol-2-ylidene), whichi sa na symmetric complex with one stronga nd one weak ligand that does not symmetrize to [PdCl 2 (IDM) 2 ]a nd [PdCl 2 (AsPh 3 ) 2 ]u nder the working conditions for that Au-cocatalyzed Stille process. Unfortunately,o ur attempts, at the be-ginningo ft his work, at extending this gold(I) cocatalysis to the Hiyama reactionhave been unsuccessful.…”
Section: Synthetic Studiesmentioning
confidence: 93%
See 1 more Smart Citation
“…This microreview reports recent advances in the use of multiple organometallic complexes applied to catalytic reactions involving at least one hydrogenation or dehydrogenation process . There are multiple‐metal‐catalysed processes in which the hydrogen released in the first catalytic cycle is then used for a catalytic hydrogenation reaction in a second catalytic cycle.…”
Section: Introductionmentioning
confidence: 99%